2008
DOI: 10.1002/pssb.200879631
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of C4+ irradiated single‐walled carbon nanotube paper

Abstract: Single‐walled carbon nanotube (SWNT) networks have been irradiated with a 12C4+ ion beam (ion energy 23 MeV) to investigate changes to their properties. Measurements of the Raman D‐line show that the irradiation produces structural defects throughout SWNT paper of thickness 40 μm, with a linear increase in defects at the back side of the sample, but a saturating tendency occurring at the front (irradiated) side. The resistance of the samples also increases linearly with irradiation dose. The temperature depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 13 publications
0
10
1
Order By: Relevance
“…It is worth noting that the maximum I (D) was previously observed at the inter-defect distance of ~3 nm for low energy (90 eV) Ar + bombardment 21 . This implies that the ion dose required to obtain the maximum I (D)/ I (G) depends on the ion species 28 , 29 . Moreover, the I (D)/ I (G) also differs for different irradiation energies.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the maximum I (D) was previously observed at the inter-defect distance of ~3 nm for low energy (90 eV) Ar + bombardment 21 . This implies that the ion dose required to obtain the maximum I (D)/ I (G) depends on the ion species 28 , 29 . Moreover, the I (D)/ I (G) also differs for different irradiation energies.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, high energy irradiation of the samples with 23 MeV C 4+ ions did not give rise to any enhancement in conductivity. 455 An increase in electrical conductivity of carbon nanotube sheets irradiated with Ar and H ions at a temperature of 800 K has also been reported. 456 The conductivity improvement was associated with the formation of covalent cross-links between nanotubes induced by the ion beam irradiation at the elevated temperature.…”
Section: Electronic Propertiesmentioning
confidence: 91%
“…15 It was shown that ion-irradiation-induced double vacancies ͑DVs͒, in comparison to single vacancies ͑SVs͒, strongly reduce the conductivity of metallic tubes. The effects of irradiation in more complicated systems, such as SWNT bundles 16 and films, 17,18 have also been studied and interesting effects such as an increase in the conductance after moderate irradiation dose have been reported. 17 In the transport experiments discussed above, only indirect information on the type of defects can be deduced.…”
Section: Introductionmentioning
confidence: 99%